2021
DOI: 10.1177/0300060520982687
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rapid on-site cytological evaluation (ROSE) by a pulmonologist in determining specimen adequacy and diagnostic accuracy in interventional diagnosis of lung lesions

Abstract: Objective To evaluate the efficacy of rapid on-site cytological evaluation (ROSE) in determining specimen adequacy and diagnostic accuracy in the interventional diagnosis of lung lesions. Methods This retrospective study included 127 consecutive cases of lung lesions, which were sampled by bronchoscopy or transthoracic fine needle aspiration, and diagnosed on ROSE followed by histopathology. ROSE was performed by a trained pulmonologist and the diagnosis of ROSE was compared with the final diagnosis. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Our findings have also been validated in several reports abroad. Some scholars have demonstrated a high rate of agreement between ROSE combined with EBUS-TBNA and the final pathological result and proved the effectiveness of ROSE in determining the quality and quantity of specimens ( 10 , 11 ). Davenport ( 12 ) reported that ROSE could increase the detection rate of specimens containing malignant cells by comparing 73 aspirates using the technique with 134 routinely processed aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have also been validated in several reports abroad. Some scholars have demonstrated a high rate of agreement between ROSE combined with EBUS-TBNA and the final pathological result and proved the effectiveness of ROSE in determining the quality and quantity of specimens ( 10 , 11 ). Davenport ( 12 ) reported that ROSE could increase the detection rate of specimens containing malignant cells by comparing 73 aspirates using the technique with 134 routinely processed aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings have also been validated in several reports abroad. Some scholars have demonstrated a high rate of agreement between ROSE combined with EBUS-TBNA and the nal pathological result and proved the effectiveness of ROSE in determining the quality and quantity of specimens 8,9 . Davenport et al 10 that ROSE could increase the detection rate of specimens containing malignant cells by comparing 73 aspirates using the technique with 134 routinely processed aspirates.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the rapid on-site cytologic evaluation will be beneficial in improving the diagnostic yield of bronchoscopy. 28 , 29 , 30 , 31 Therefore, operators should consider these factors, which may contribute to the failure of the rEBUS visualization yield entirely translated into the diagnostic yield of bronchoscopy, to narrow the difference between the two.…”
Section: Discussionmentioning
confidence: 99%